More than meets the eye: Papilledema from syphilis posing as idiopathic intracranial hypertension. (October 2020) - Chi, Sharon; Weintrob, Amy
Idiopathic intracranial hypertension (IIH), or pseudotumor cerebri, is a diagnosis of exclusion. Elevated intracranial pressure (ICP) can result from a variety of inflammatory and structural causes affecting cerebrospinal fluid production and absorption. First described in 1935, syphilis is a well-established cause of elevated ICP, referred to as syphilitic hydrocephalus. We report a case of a 49-year-old man presenting with vision changes and headache who was treated for IIH without resolution of symptoms, and eventually diagnosed with syphilitic hydrocephalus. Syphilis should be considered as a cause of elevated ICP prior to a diagnosis of IIH.